Unsupervised Pathological Area Extraction Using 3D T2 and FLAIR MR Images - Dvořák, Pavel; Bartušek, Karel; Smékal, Zdeněk (Walter de Gruyter, 2014)
This work deals with fully automated extraction of brain tumor and edema in 3D MR volumes. The goal of this work is the extraction of the whole pathological area using such an algorithm that does not require a human intervention. For the good visibility of these kinds of tissues both T2-weighted and FLAIR images were used. The proposed method was tested on 80 MR volumes of publicly available BRATS database, which contains high and low grade gliomas, both real and simulated. The performance was evaluated by Dice coefficient, where the results were differentiated between high and low grade and real and simulated gliomas. The method reached promising results for all of the combination of images: real high grade (0.73), real low grade (0.81), simulated high grade (0.81), simulated low grade (0.81).

This work deals with fully automated extraction of brain tumor and edema in 3D MR volumes. The goal of this work is the extraction of the whole pathological area using such an algorithm that does not require a human intervention. For the good visibility of these kinds of tissues both T2-weighted and FLAIR images were used. The proposed method was tested on 80 MR volumes of publicly available BRATS database, which contains high and low grade gliomas, both real and simulated. The performance was evaluated by Dice coefficient, where the results were differentiated between high and low grade and real and simulated gliomas. The method reached promising results for all of the combination of images: real high grade (0.73), real low grade (0.81), simulated high grade (0.81), simulated low grade (0.81).
Unsupervised Pathological Area Extraction Using 3D T2 and FLAIR MR Images
Keywords: Brain tumor; Brain tumor segmentation; Extraction; Magnetic Resonance; MRI; Pathology; Segmentation; Symmetry analysis.; Brain tumor; Brain tumor segmentation; Extraction; Magnetic Resonance; MRI; Pathology; Segmentation; Symmetry analysis.